Nuances of Microsurgical and Endoscope Assisted Surgical Techniques to the Cranio-Vertebral Junction: Review of the Literature - Visocchi Massimiliano; Signorelli Francesco; Iacopino Gerardo; Barbagallo Giuseppe (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2017)
Purpose: An update of the technical nuances of microsurgical - endoscopic assisted approaches to the craniocervical junction (transnasal, transoral and transcervical) if provided from the literature in order to better contribute to identify the best strategy. Methods: A non-systematic update of the review and reporting on the anatomical and clinical results of endoscopic assisted and microsurgical approaches to the craniocervical junction (CVJ) is performed. Results: Pure endonasal and cervical endoscopic approaches still have some disadvantages,including the learning curve and the deeper surgical fi eld. Endoscopically assisted transoral surgery with 30° endoscopes represents an emerging option to standard microsurgical techniques for transoral approaches to the anterior CVJ. This approach should be considered as complementary rather than an alternative to the traditional transoral-transpharyngeal approach. Conclusions: Transoral (microsurgical or video-assisted) approach with sparing of the soft palate still remains the gold standard compared to the ''pure'' transnasal and transcervical approaches due to the wider working channel provided by the former technique. Transnasal endoscopic approach alone appears to be superior when the CVJ lesion exceeds the upper limit of the inferior third of the clivus. Of particular interest the evidence that advancement in reduction techniques can avoid ventral approach.